2002
DOI: 10.1590/s0100-84042002000200009
|View full text |Cite
|
Sign up to set email alerts
|

Síndromes de dispersão de espécies arbustivo-arbóreas em cerrado sensu stricto do Brasil Central e savanas amazônicas

Abstract: -(Dispersal syndromes of shrub-woody species in the cerrado sensu stricto vegetation of Central Brazil and amazonian savannas). The objective was to identify the proportion of seed dispersion syndromes in areas of cerrado sensu stricto of Central Brazil and amazonian savannas. Lists of species of nine cerrado and five amazonian savanna areas were used. Dispersion syndromes were determined through literature data. Chi-square test (χ 2 ) was used to evaluate possible differences in proportion of zoocory and anem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1
20

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 11 publications
3
12
1
20
Order By: Relevance
“…) demonstrated that specific seed dispersal syndrome. Vieira et al (2002) and Griz et al (2002) likewise found that anemochorous species develop better in open areas (which are normally drier environments) than in forest sites.…”
Section: Discussionmentioning
confidence: 97%
“…) demonstrated that specific seed dispersal syndrome. Vieira et al (2002) and Griz et al (2002) likewise found that anemochorous species develop better in open areas (which are normally drier environments) than in forest sites.…”
Section: Discussionmentioning
confidence: 97%
“…Martins et al (2004), em áreas de Cerrado stricto sensu em Itirapina, SP, encontraram maior proporção de espécies zoocóricas (58,6%) do que de anemocóricas (28,6%), enquanto as espécies autocóricas também apresentaram as menores proporções (12,8%). Já Vieira et al (2002), estudando áreas de Cerrado stricto sensu no Brasil central e áreas de savanas amazônicas, relataram que a zoocoria ocorreu com maior frequência tanto no Cerrado quanto nas áreas de savanas amazônicas estudadas, com proporções entre 51,1 e 68,3% de espécies zoocóricas, contra 26,7 a 46,7% de espécies anemocóricas, respectivamente. Os resultados aqui encontrados indicam a importância da zoocoria para essa área.…”
Section: Discussionunclassified
“…The proportion of zoochorous plant species is high in both savanna and forest physiognomies of the Cerrado. In the Cerrado sensu stricto of Central Brazil, for example, the proportion of zoochorous plant species ranges from 51 to 68% (Vieira et al 2002). On the other hand, in the Gallery Forests of Central and Southeastern Brazil, 63 to 89% of the plants have zoochorous dispersion and more than half of them are ornithochorous (Pinheiro & Ribeiro 2001, Motta-Junior & Lombardi 2002.…”
Section: Introductionmentioning
confidence: 99%